Investigations of physicochemical properties of bottom-ash materials for use them as secondary raw materials; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Malchik A. G. Aleksandra Gennadievna (Environmental protection, industrial labor safety, 2015)
Title screen